SOCIO-PSYCHOLOGICAL ASPECTS OF STUDYING PATIENTS WITH LICHEN PLANUS (World Bulletin of Public Health, 2023)
Adaptation of patients with lichen planus into society is difficult for many reasons. In 90% of cases, the disease is localized in open areas of the skin and is a cosmetic defect, clearly visible to others. The sight of patients causes fear, anxiety, hostility, disgust in relatives, friends, work colleagues, random people. Patients with lichen planus have a hard time with such an inadequate attitude towards themselves, withdraw into themselves, avoid contacts, communication with friends and, especially, strangers . Contributing to social disadaptation and defensiveness is formed, leading to problems both in personal life and in professional activities and careers